PENGENDALIAN PERSEDIAAN YANG EFEKTIF PADA PT SURYA MEGA MUSTIKA - Surjadi, Lukman; Theodorus, Valerie Theresa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
PT Surya Mega Mustika is a company engaged in the business of printing and printing has problems with inventory. The reason is that there are several deficiencies in the company's inventory control so that there is too much investment in inventory, empty inventory when needed, so that there is no stock taking to determine the company's final inventory amount. This resulted in the company's profit not being maximized, lack of asset turnover, and fraud. The PKM team provides a solution in the form of counseling on inventory control for companies to avoid excessive inventory buildup and has an impact on high storage costs, so that the goods become expired or stolen which can cause losses, namely in several ways, including carrying out internal inventory control by compiling a production budget and EOQ by taking into account waiting time and safety stock so that when high demand supplies are available so that profit remains maximized. The solution to this problem will be delivered in the form of an online Community Service (PKM) presentation through the Zoom Meeting application. The results of this PKM are mandatory outputs entitled